Effect of zinc supplementation on morbidity among stunted children in Indonesia - Rustam Siregar; Lilisianawati Lilisianawati; Endang Dewi Lestari; Harsono Salimo (Indonesian Pediatric Society Publishing House, 2011)
Background The Indonesian Health Ministry reported that 35 .6% of Indonesian children and up to 50% in certain regions have stunted growth. They are at high risk of chronic zinc deficiency. Inadequate zinc intake may result in an impaired immune sy stem and high incidence of morbidity. Zinc supplementation is knO\Vll to improve immune status thus reducing the incidence of morbidity among stunted children. Objective To evaluate the effects of zinc supplementation on morbidity incidence among stunted Indonesian school children.  Methods We evaluated the effects of daily zinc supplementation (2.38 mg of zinc􀁇supplemented milk) on the incidence of diarrhea, respiratory infections, and fever in a double􀁇blind, randomized, controlled trial in 169 stunted children (zinc􀁇supplemented n=84; placebo n=85) aged 7 to 9 years in Jakarta and Solo. Zinc supplementation and morbidity surveillance were perfonned for 6 months. Results Compared to the first 3 months of intervention, zinc supplementation resulted in a reduction in the incidence of diarrhea, respiratory infections, and fever during the second three months (by 67%, 42%, and 30%, respectively). Children from the zinc􀁇supplemented group tended to have a lower episodic incidence of diarrhea and fever than those from the placebo group, although neither of these differences was statistically significant (P< 0.45,95% CI 0.63 to 0.89). Conclusion Zinc supplementation has no significant effect in reducing the incidence of diarrhea, respiratory infections, and fever in stunted children although tended to have a lower episodic incidence.